Late medieval decorative arts in a bourgeois milieu. Ornamented stove tiles with Italian garlands from Cluj-Napoca - Ilka Boér (Anastasis: Research in Medieval Culture and Art)
The article deals with a group of late medieval decorative stove tiles discovered in Cluj-Napoca. A considerable part of the revealed materials at the site at the Unitarian Episcopal House bears a rich Renaissance floral ornament, an Italian garland, which surrounds a rosette of varied forms. These ornamental fragments were categorized into six different types, and dated to the second half – the end of the 16th century. Related to the material, the alike motives on stove tiles are discussed from Transylvania and Hungary with some examples from western Europe too.